Perfluorochemical‐facilitated plasminogen activator delivery to the airways: A novel treatment for inhalational smoke‐induced acute lung injury. Issue 1 (30th April 2020) - Wolfson, Marla R.; Enkhbaatar, Perenlei; Fukuda, Satoshi; Nelson, Christina L.; Williams, Robert O.; Surasarang, Soraya Hengsawas; Sahakijpijarn, Sawittree; Calendo, Gennaro; Komissarov, Andrey A.; Florova, Galina; Sarva, Krishna; Idell, Steven I.; et al.
Abstract: Background: Effective clinical management of airway clot and fibrinous cast formation of severe inhalational smoke‐induced acute lung injury (ISALI) is lacking. Aerosolized delivery of tissue plasminogen activator (tPA) is confounded by airway bleeding; single‐chain urokinase plasminogen activator (scuPA) moderated this adverse effect and supported transient improvement in gas exchange and lung mechanics. However, neither aerosolized plasminogen activator (PA) yielded durable improvements in physiologic responses or reduction in cast burden. Here, we hypothesized that perfluorochemical (PFC) liquids would facilitate PA distribution and sustain improvements in physiologic outcomes in ISALI. Methods: Spontaneously breathing adult sheep (n = 36) received anesthesia and analgesia and were instrumented, exposed to cotton smoke inhalation, and supported by mechanical ventilation for 48 h. Groups (n = 6/group) were studied without supplemental treatment, or, starting 4 h post injury, they received intratracheal low volume (8 mL) PFC liquid alone or a dose range of tPA/PFC or scuPA/PFC suspensions (4 or 8 mg in 8 mL PFC) every 8 h. Outcomes were evaluated by sequential measurements of cardiopulmonary parameters, lung histomorphology, and biochemical analyses of bronchoalveolar lavage fluid. Results: Dose‐response and PA‐type comparisons of outcomes demonstrated sustained superiority with low‐volume PFC suspensions of scuPA over tPA or PFC alone, favoring the highest dose of scuPA/PFC suspension over lower doses, without airway bleeding. Conclusions: We propose that this improved profile over previously reported aerosolized delivery is likely related to improved dose distribution. Sustained salutary responses to scuPA/PFC suspension delivery in this translational model are encouraging and support the possibility that the observed outcomes could be of clinical importance.